PENGALAMAN KOMUNIKASI JARAK JAUH ANTARA ANAK DENGAN ORANG TUA: Studi Pada Mahasiswa Rantau FISIP UPNVJ 2018. - Lastria Ulfanissah (2022)
This research is motivated by the situation that in general children and parents communicate directly and face to face, but this is different from what happened to students who migrated to communicate with their parents due to long distances. This study aims to examine the experience of long-distance communication between children (overseas students of FISIP UPNVJ 2018) and their parents. This study uses a qualitative method with a phenomenological approach. Data collection uses in-depth interviews with informants using two ways, namely online and offline due to the constrained spread of COVID-19. The number of informants taken in this study was 7 people from 3 different study programs at FISIP UPNVJ. Data analysis techniques used in the study include; collection of life experiences, horizontalization, significant statements, thematic analysis, essence statements. Based on the research, it can be concluded that students communicate using mobile phones and whatsapp applications, while they experience obstacles in communicating, namely signal and time barriers. During this long-distance communication, students feel that there is a change in the way of communication and relationship (closeness) with parents after becoming overseas children.